Excess protons in water-acetone mixtures. II. A conductivity study - Semino, Rocio (2013)
In the present work we complement a previous simulation study "R. Semino and D. Laria, J. Chem. Phys. 136, 194503 (2012)" on the disruption of the proton transfer mechanism in water by the addition of an aprotic solvent, such as acetone. We provide experimental measurements of the mobility of protons in aqueous-acetone mixtures in a wide composition range, for water molar fractions, xw, between 0.05 and 1.00. Furthermore, new molecular dynamics simulation results are presented for rich acetone mixtures, which provide further insight into the proton transport mechanism in water-non-protic solvent mixtures. The proton mobility was analyzed between xw 0.05 and 1.00 and compared to molecular dynamics simulation data. Results show two qualitative changes in the proton transport composition dependence at x w ∼ 0.25 and 0.8. At xw < 0.25 the ratio of the infinite dilution molar conductivities of HCl and LiCl, Λ 0HCl.Λ0LiCl-1, is approximately constant and equal to one, since the proton diffusion is vehicular and equal to that of Li+. At xw ∼ 0.25, proton mobility starts to differ from that of Li+ indicating that above this concentration the Grotthuss transport mechanism starts to be possible. Molecular dynamics simulation results showed that at this threshold concentration the probability of interconversion between two Eigen structures starts to be non-negligible. At xw ∼ 0.8, the infinite molar conductivity of HCl concentration dependence qualitatively changes. This result is in excellent agreement with the analysis presented in the previous simulation work and it has been ascribed to the interchange of water and acetone molecules in the second solvation shell of the hydronium ion.